(untitled) (Communications in Computational Physics, 2018)
A three-field smoothed formulation is proposed in this paper for the resolution of fluid-structure interaction (FSI) from the arbitrary Lagrangian–Eulerian perspective. The idea behind the proposed approach lies in different smoothing concepts. Both fluid and solid stress tensors are smoothly treated by the cell-based smoothed finite element method (CS-FEM) using four-node quadrilateral elements. In particular, the smoothed characteristic-based split technique is developed for the incompressible flows whereas the geometrically nonlinear solid is settled through CS-FEM as usual. The deformable mesh, often represented by a pseudo-structural system, is further tuned with the aid of a hybrid smoothing algorithm. The Explicit Relaxed Interface Coupling (ERIC) scheme is presented to interpret the nonlinear FSI effect, where all interacting fields are explicitly coupled in alliance with interface relaxation method for numerical stability. The promising ERIC solver is in detail validated against the previously published data for a large-displacement FSI benchmark. The good agreement is revealed in computed results and well-known flow-induced phenomena are accurately captured.